Effect of metal-reinforced UV-O3-TETA functionalized MWCNTs on thermomechanical and radiation-resistant properties of PMMA. (September 2020) - Raza, Ramsha; Ahmed, Fiaz; Khan, Asim; Iftikhar, Muhammad; Abbas, Syed Mustansar; Ali, Saqib
Graphical abstract: Highlights: MWCNTs modified by UV-O3 and TETA treatment for use as a reinforcement for PMMA. Silver metal nanoparticles are deposited on UV-O3 -TETA-MWCNTs using two approaches. Nanocomposites show better radiation resistance and thermomechanical stability. The flow of irradiated energy is highly dependent on the concentration of MWCNTs. Ag/UV-O3 -TETA-MWCNTs/PMMA(0.25%) show major reinforcing impact on PMMA degradation. Abstract: In this work multiwall carbon nanotubes (MWCNTs) oxidized with UV-O3 are functionalized with triethylenetetramine (TETA) moiety. A new type of radiation-protective nanocomposite films has been fabricated by free radical polymerisation of methyl methacrylate (MMA) in the presence of the metal-supported, chemically functionalized and highly dispersed MWCNTs, while the long-chain amides, grafted on the MWCNTs surface provide anchorage site for deposits of Ag nanoparticles. The nanocomposite films have been characterized to understand the structural and morphological characteristics, mechanical stability, and thermal resistance. The structural and microscopic features show the homogeneous distribution of MWCNTs in the PMMA matrix that increases the thermal stability, thermo-mechanical strength, thermal conductivity and glass transition temperatures of nanocomposite films, even with the addition of 0.25 wt% of modified nano-fillers. The thermal and thermo-mechanical characteristics of nanocomposites before and after irradiation have been compared with that of pure PMMA and the findings indicate that the high-energy radiation can be efficiently dispersed through the Ag/UV-O3 -TETA-MWCNTs/PMMA network and has a significant reinforcing impact on nature of PMMA degradation.